A web-based psychoeducational simulation game for adults in stepfamilies (GSteps)—study protocol for a randomized controlled feasibility trial - Santos, Carina Mota; Costa, Maria Emília; Higginbotham, Brian Jensen; Martins, Mariana Veloso (Frontiers in Psychology, 2022)
Background: Stepfamilies are a prevalent family form. However, stepfamilies are less stable than nuclear, first-marriage families due to the presence of risk factors such as the absence of social norms and the presence of stepchildren. Stepfamilies have unique educational needs regarding stepparenting and co-parenting issues. The development and documentation of psychoeducational intervention strategies can facilitate dissemination of ongoing studies and promote transparency. This article describes the background, design and protocol of a randomized controlled trial (RCT) evaluating the effectiveness and feasibility of a web-based Psychoeducational Simulation Game (GSteps). Behavior-modeling video training (BMT) is used to demonstrate and promote relational skills, stepparenting and co-parenting effective strategies for adults in stepfamilies. A mental health professional will be available within the GSteps platform for clarification or emotional support. Methods/Design: A RCT design is presented to evaluate the outcomes of a self-administered, interactive and web-based psychoeducational Game targeting dyadic marital adjustment and interpersonal skills as the primary outcomes and remarriage beliefs, family function and stepparenting and co-parenting attitudes as the secondary outcomes. Other outcome measures include satisfaction with GSteps and participants' knowledge learned after the intervention. The minimum required sample size is 112 participants (56 per condition) randomly allocated either to an experimental group (EG), receiving GSteps intervention, or to a wait-list control group (CG). A survey is conducted electronically. Assessments take place at baseline (T0), after the intervention (T1) and 1-month follow-up (T2). Discussion: This protocol presents a RCT aimed at evaluating the efficacy of a web-based psychoeducational intervention (GSteps) designed for improving marital, stepparenting and co-parenting skills in adults who live in stepfamilies. The use of the protocol and results of intervention studies may guide the use and refinement of web-based psychoeducational intervention for stepfamilies. Additionally, GSteps may become a tool for health professionals to enhance stepfamily functioning, stepparenting skills, and marital adjustment of remarried adults.